Laser polishing of additive manufactured Ti alloys - Ma, C. P. (2018)
Laser-based additive manufacturing has attracted much attention as a promising 3D printing method for metallic components in recent years. However, surface roughness of additive manufactured components has been considered as a challenge to achieve high performance. In this work, we demonstrate the capability of fiber laser in polishing rough surface of additive manufactured Ti-based alloys as Ti-6Al-4V and TC11. Both as-received surface and laser-polished surfaces as well as cross-section subsurfaces were analyzed carefully by White-Light Interference, Confocal Microscope, Focus Ion Beam, Scanning Electron Microscopy, Energy Dispersive Spectrometer, and X-ray Diffraction. Results revealed that as-received Ti-based alloys with surface roughness more than 5 µm could be reduce to less than 1 µm through laser polishing process. Moreover, microstructure, microhardness and wear resistance of laser-polished zone was investigated in order to examine the thermal effect of laser polishing processing on the substrate of additive manufactured Ti alloys. This proof-of-concept process has the potential to effectively improve the surface roughness of additive manufactured metallic alloy by local polishing method without damage to the substrate.